Use of Image Media to Increase Early Childhood Reading Interest - Dimrayani, Dimrayani; Herlina, Herlina; Bachtiar, Muhammad Yusri; Wahira, Wahira (PT. Riset Press International, 2025)
Image media is a medium that can increase children's interest in reading and communication. Image media can be stimulated to develop optimally. One of the developments in reading interest to children is through picture media. The importance of picture media for children is that it can increase knowledge and make it easier for children to communicate with others. The purpose of this study is to find out which Image Media can increase reading interest in children in kindergarten. This study uses qualitative descriptive research with teacher and student research subjects. The data collection tools used by the author in the research are observation, interviews, and documentation. By using this analysis, the researcher presented the results of the study that developing an interest in reading through picture media in kindergarten, in general, has developed the observation based on the 5 indicators presented by the researcher. This development has been in line with expectations. Based on the results of this analysis, in following the image media of 5-6-year-old children in kindergarten, it can be concluded that everything develops optimally.